2005
DOI: 10.2116/analsci.21.845
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Incidence-X-ray Fluorescence Spectrometry for the Compositional Analysis of Nanometer-Thin High-κDielectric HfO2 Layers

Abstract: In future microelectronic devices, SiO2 as a gate dielectric material will be replaced by materials with a higher dielectric constant. One such candidate material is HfO2. Thin layers are typically deposited from ligand-containing precursors in chemical vapor deposition (CVD) processes. In the atomic layer deposition (ALD) of HfO2, these precursors are often HfCl4 and H2O. Obviously, the material properties of the deposited films will be affected by residual ligands from the precursors. In this paper, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…As the TXRF is being used to characterize the new films being introduced into the semiconductor process line and to monitor for cross contamination from these new materials [14][15][16][17][18], nanoliter depositions can be used with TXRF to improve upon the characterization process. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the TXRF is being used to characterize the new films being introduced into the semiconductor process line and to monitor for cross contamination from these new materials [14][15][16][17][18], nanoliter depositions can be used with TXRF to improve upon the characterization process. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…conventional TXRF, is preferable however in terms of simplicity and speed. Validation studies with RBS as a reference demonstrated that for dense layers on lighter substrates, such as HfO 2 on Si substrates, the TXRF approach is limited to layers <1 nm due to saturation effects, as reported before (9). In this study we extended the investigation for light layers on denser substrates, such as a passivation layer of Si on Ge.…”
Section: Characterization Of S-(sub)monolayer Passivation Layers On Gementioning
confidence: 62%
“…Whereas before only Si and SiO 2 wafers were measured, now a whole range of materials as wafers or layers have been reported in research and development applications: silicon nitride [102,103], siliconon-insulator (SOI) [104], Ge [105,106], GaAs [107,108], HfO 2 [109][110][111], Al 2 O 3 [110,111], Ta 2 O 5 [112], polymer layers [113] and other unpublished materials. Both procedures for Direct-TXRF and VPD-DC-TXRF have been reported.…”
Section: Novel Applications At Materials Levelmentioning
confidence: 99%
“…A first characteristic of interest for layered materials is in the coverage of the material constituent on the bulk substrate. TXRF has been applied to characterize deposition processes of for example gate dielectrics [109][110][111]114], with a clear advantage of accessibility, user friendliness and related learning speed compared to established techniques such as Rutherford backscattering spectrometry (RBS). Fig.…”
Section: Direct-txrfmentioning
confidence: 99%
See 1 more Smart Citation